The application of Artificial Intelligence in the tourism industry: a systematic literature review based on prisma methodology - Henriques, Henrique (2024)
Tourism is one of the biggest industries in the world and its contribution to the global economy has continued to grow. Due to the rapid development of technology, tourism has seen some critical changes in how people interact with the industry. By applying artificial intelligence (AI) to different aspects of the tourism business, it is possible to increase efficiency by using resources more effectively. This paper aims to provide insights into how AI technologies can be applied to different aspects of tourism operations and services to improve the customer experience both online and offline and at service providers such as hotels. A literature review is conducted based on the PRISMA methodology by running searches on databases Scopus and Web of Science. This research contributes to providing an overview of how current AI technologies are used in the tourism industry and how they may be used in the fu- ture to enhance customers' experiences when interacting with different aspects of tourism. It also examines various concerns that need further investigation before adoption can occur. The review shows that the application of AI technologies can improve numerous facets of tourism operations and services, resulting in numerous advantages.